Digitized local content: a tool for cultural preservation and transmission (2007)
This paper sought to expound on how the African local content can be successfully digitized and used as a tool in preserving and transmitting African culture by providing answers to four major questions as follows: What is local content? Why do we need to digitize our local content? How do we digitize local content? And how do we use the digitized local content to preserve and transmit African traditions and culture to the outside world? Furthermore, constraints to digitizing and transmitting African local content were also identified. However, the paper concluded and made recommendations on how Nigeria can join the rest of Africa in improving and promoting our local content in the Global Information Infrastructure (GII) which is seen presently to be minimal (0.4%) (UNECA, 1999).